2018
DOI: 10.1038/s41598-018-29760-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of serum biomarkers in hemodialysis patients with mild cognitive decline: A prospective single-center cohort study

Abstract: Studies suggest that hemodialysis patients are at a higher risk for cognitive decline than healthy individuals; however, underlying mechanisms have not been fully elucidated. We aimed to investigate the roles of serum biomarkers, such as brain-derived neurotrophic factor (BDNF), inflammatory cytokines, fibroblast growth factor (FGF)-23 and its co-receptor α-klotho and platelet (PLT) count in mild cognitive decline (MCD) of patients undergoing hemodialysis in this prospective cohort study. Serum levels of BDNF,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 42 publications
0
6
0
1
Order By: Relevance
“…Additionally, microvascular renal injury is a prominent feature of diabetes and hypertension, known as common causes of CKD and cognitive impairment [ 37 ]. Other mechanisms involve oxidative stress and inflammation, since increased serum levels of free radicals and pro-inflammatory cytokines, including interleukin-6 (IL-6), tumor necrosis factor (TNF), and IL-1beta, contribute to both CKD progression [ 38 , 39 ] and neuroinflammation [ 40 ]. Additionally, serum levels of neuropeptide Y (NPY), parathormone (PTH), and fibroblast growing factor 23 (FGF 23) are commonly increased in CKD and seem to promote endothelial dysfunction in brain microcirculation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, microvascular renal injury is a prominent feature of diabetes and hypertension, known as common causes of CKD and cognitive impairment [ 37 ]. Other mechanisms involve oxidative stress and inflammation, since increased serum levels of free radicals and pro-inflammatory cytokines, including interleukin-6 (IL-6), tumor necrosis factor (TNF), and IL-1beta, contribute to both CKD progression [ 38 , 39 ] and neuroinflammation [ 40 ]. Additionally, serum levels of neuropeptide Y (NPY), parathormone (PTH), and fibroblast growing factor 23 (FGF 23) are commonly increased in CKD and seem to promote endothelial dysfunction in brain microcirculation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study in 605 patients with advanced CKD, investigating 25OHD, 1,25OHD, PTH, and FGF23, suggests that dysregulation in mineral metabolism does not contribute to impaired cognitive function in these patients. A single-center cohort study comparing 20 healthy individuals with 58 patients on chronic hemodialysis, sub-grouped in patients with normal cognitive function (NCF) and those with mild cognitive decline (MCD), shows significant differences between circulating FGF23 and Klotho levels in hemodialysis patients compared to healthy controls, but not between patients with NCF and MCD, suggesting that hemodialysis-related MCD is not related to altered FGF23 and Klotho [32]. Finally, a cross-sectional observational study in 69 hemodialysis patients recently demonstrated an association of cognitive impairment with intracranial artery calcification and low FGF23.…”
Section: Fgf23 and Cognitive Impairment In Ckdmentioning
confidence: 99%
“…Predloženi su i neki biomarkeri koji bi mogli poslužiti za prepoznavanje kognitivnih poremećaja kod pacijenata na hemodijalizi kao što su BDNF, TNF-α i IL-6, kao i broj trombocita u krvi [31,32] .…”
Section: Dijanostički Pristup Kognitivnim Poremecajima I Demenciji Kod Pacijenata Na Hemodijaliziunclassified